PENGARUH KONSEP DIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN KENARI 07 PAGI JAKARTA - Manurung, Alberth Supriyanto (Eduscience : Jurnal Ilmu Pendidikan, 2020)
Abstract The purpose of this study was to determine the Effect of Self Concepts on Student Learning Outcomes of Grade IV SDN Kenari 07 Pagi. The research method used was a survey method and used simple regression and correlation analysis techniques, multiple regression and correlation. This research was conducted at SDN Kenari 07 Pagi Jakarta, Senen sub-district, Central Jakarta with n = 70 using the Cluster Sampling technique. This research is based on the following hypotheses: (1) Self-concept has a contribution to the learning outcomes of mathematics; (2) Interest has an influence on self-concept; (3) The student's background has an influence on self-concept; (4) Intelligence has influence with self-concept; (5) There is an influence between talent and self-concept and mathematics learning outcomes. Based on this research it is expected that the mathematics learning outcomes of Grade IV students can be improved by the influence of self-concept, because the verification results prove that self-concept is a significant determining factor.Keywords: self-concept, mathematics learning outcomes and influenceÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â